Kepemimpinan Kepala Sekolah Berwawasan Visioner-Transformatif dalam Otonomi Pendidikan - Rasmianto, Rasmianto (UIN Maulana Malik Ibrahim Malang, 2003)
Leadership of the principal has an active role in improving the quality of education so that he is required to have good leadership skills Because good school leadership is capable and able to manage all educational resources to achieve educational goals both in terms of learning and human resource development. So that the principal is also required to be able to create a good organizational climate so that all components of the school can portray themselves together to achieve the goals and objectives of the school organization. The principal must be able to provide the role of an inspiring, inspiratory, participatory, and motivator to teachers, students and employees to create synergy to improve the institution's performance in achieving the expected goals and objectives. Kepemimpinan kepala sekolah mempunyai peran aktif dalam meningakatkan kualitas pendidikan sehingga ia diharuskan memiliki kemampuan memimpin yang baik Sebab, kepemimpinan sekolah yang baik adalah yang mampu dan dapat mengelola semua sumber daya pendidikan untuk mencapai tujuan pendidikan baik dari sisi pembelajaran maupun pengembangan sumber daya manusia. Sehingga kepala sekolah juga dituntut untuk mampu menciptakan iklim organisasi yang baik agar semua komponen sekolah dapat memerankan diri secara bersama untuk mencapai sasaran dan tujuan organisasi sekolah. Kepala sekolah harus mampu memberikan peran sebagai seorang insiator, inspiratosr, partisipator, dan motivator kepada guru, siswa, dan karyawan untuk sama-sama menciptakan sinergisitas untuk meningkatkan kinerja lembaga dalam mencapai tujuan dan sasaran yang diharapkan.